AMPK Activity Contributes to G2 Arrest and DNA Damage Decrease via p53/p21 Pathways in Oxidatively Damaged Mouse Zygotes - He, Pei; Li, Zhiling; Xu, Feng; Ru, Gaizhen; Huang, Yue; Lin, En; Peng, Sanfeng (Frontiers in Cell and Developmental Biology, 2020)
In zygotes, the capacity of G2/M checkpoint and DNA repair mechanisms to respond to DNA damage varies depending on different external stressors. In our previous studies, we found that mild oxidative stress induced a G2/M phase delay in mouse zygotes fertilized in vitro, due to the activation of the spindle assembly checkpoint. However, it is unclear whether the G2/M phase delay involves G2 arrest, triggered by activation of the G2/M checkpoint, and whether AMPK, a highly conserved cellular energy sensor, is involved in G2 arrest and DNA damage repair in mouse zygotes. Here, we found that mouse zygotes treated with 0.03 mM H2O2 at 7 h post-insemination (G1 phase), went into G2 arrest in the first cleavage. Furthermore, phosphorylated H2AX, a specific DNA damage and repair marker, can be detected since the early S phase. We also observed that oxidative stress induced phosphorylation and activation of AMPK. Oxidative stress-activated AMPK first localized in the cytoplasm of the mouse zygotes in the late G1 phase and then translocated to the nucleus from the early S phase. Overall, most of the activated AMPK accumulated in the nuclei of mouse zygotes arrested in the G2 phase. Inhibition of AMPK activity with Compound C and SBI-0206965 abolished oxidative stress-induced G2 arrest, increased the activity of CDK1, and decreased the induction of cell cycle regulatory proteins p53 and p21. Moreover, bypassing G2 arrest after AMPK inhibition aggravated oxidative stress-induced DNA damage at M phase, increased the apoptotic rate of blastocysts, and reduced the formation rate of 4-cell embryos and blastocysts. Our results suggest the G2/M checkpoint and DNA repair mechanisms are operative in coping with mild oxidative stress-induced DNA damage. Further, AMPK activation plays a vital role in the regulation of the oxidative stress-induced G2 arrest through the inhibition of CDK1 activity via p53/p21 pathways, thereby facilitating the repair of DNA damage and the development and survival of oxidative stress-damaged embryos. Our study provides insights into the molecular mechanisms underlying oxidative-stress induced embryonic developmental arrest, which is crucial for the development of novel strategies to ensure viable embryo generation.